Family Resilience in Combating Online Gambling Issues in the Digital Era - Wisnu Cahyo Handono; Puspitasari Puspitasari (Jurnal Impresi Indonesia, 2026)
This study examines the strategic role of family resilience as a fundamental element of national resilience in the face of modernization. The family, as the smallest unit and foundation of national resilience, faces new threats in the digital era where homes are no longer fully safe due to device infiltration. Online gambling has emerged as the largest digital social pathology, damaging the family's economic, protective, and socialization functions. Modernization is impacting many areas from shifts in economic and social dynamics to changes in cultural beliefs, hence families are increasingly finding it difficult to maintain their integrity and roles. The research demonstrated how healthy family structures could potentially foster stability by fostering character, morality, productivity, and civic consciousness among individuals and possibly affect a nation. Via using a qualitative-descriptive method, the paper underlines how family resilience acts as a buffer against the negative consequences of modern depravity including moral degradation and identity crises. As such, building a resilient nation in the present depends on improving family resilience by means of valued education, religious and cultural reinforcement, as well as supportive government policies.